BMI, Physical Activity, Sleep Quality, Eating Attitudes, Emotions: Which One is Affected by Mindful Eating? BMI, Physical Activity, Mindful Eating - Köse, Gizem; Tayfur, Muhittin (Progress in Nutrition, 2021)
Present study, it was aimed to examine the eating attitude and mindful eating status of students and to examine the change of mindful eating status’ besides informing with nutrition course. The study was executed by 318 healthy students aged 18-45 years, randomly selected among students studying at Uskudar University between September 2015 and May 2016. In addition to a survey form containing personal and health information of the students, the Eating Attitudes Test (EAT-40) was conducted by Savasir and Erol, and the Mindful Eating Questionnare-30 (MEQ-30) scale conducted by Turkish Kose et al. The mean age of the participants was 21.56 ± 3.82 year. The mean score of the participants’ EAT-40 score was found to be 24.22 ± 13.98 and the mean score of the MEQ was 98.11 ± 13.81. As the EAT-40 scores decreased, MEQ scores increased, but this relationship was not statistically significant (p> 0.05). It has been shown that 28.9% of students have an eating disorder risk. There was no statistically significant difference between men’s (23.33 ± 15.60) and women’s (24.48 ± 13.50) mean EAT-40 scores (p>0.05).  Overweight-obese group was found to be having higher EAT-40 scores than the other BMI classes (p